Clinical Relevance of Serum Kyn/Trp Ratio and Basal and IFNγ-Upregulated IDO1 Expression in Peripheral Monocytes in Early Stage Melanoma - Meireson, Annabel; Ferdinande, Liesbeth; Haspeslagh, Marc; Hennart, Benjamin; Allorge, Delphine; Ost, Piet; Sundahl, Nora; Spaas, Mathieu; Demeyer, Annelies; Brochez, Lieve (Frontiers in Immunology, 2021)
Immune escape is an early phenomenon in cancer development / progression. Indoleamine 2,3-dioxygenase 1 (IDO1) is a normal endogenous mechanism of acquired peripheral immune tolerance and may therefore be tumor-promoting. This study investigated the clinical relevance of IDO1 expression by immune cells in the lymph nodes and blood and of the serum kynurenine/tryptophan (Kyn/Trp) ratio in 65 systemic treatment naïve stage I-III melanoma patients. Blood samples were collected within the first year of diagnosis. Patients had a median follow-up of 61 months. High basal IDO1 expression in peripheral monocytes and low IFNγ-induced IDO1 upregulation correlated with worse outcome independent from disease stage. Interestingly studied factors were not interrelated. During follow-up, the risk of relapse was 9% (2/22) in the subgroup with high IFNγ-induced IDO1 upregulation in monocytes. In contrast, if IDO1 upregulation was low, relapse occurred in 30% (3/10) of patients with low basal IDO1 expression in monocytes and in 61.5% (8/13) in the subgroup with high basal IDO1 expression in monocytes (Log-Rank test, p=0.008). This study reveals some immune features in the blood of early stage melanoma that may be of relevance for disease outcome. These may offer a target for sub-stratification and early intervention.